The Myriad Faces of Heroes and Heroines
XIV, 193 p. 33 illus., 29 illus. in color.
Keywords: This collection scrutinizes the representation, dynamics, transformation and/or adaptation of various heroes and heroines in different folkloric traditions and narratives in the context of Asia. Exploring notions in the topics of mythologies, folktales, literature, theatre performance and any other art forms, the volume collates discussions on the pragmatic and aesthetic representation of men and women within the mythic world, and within contemporary settings. In doing so, it produces a contemporary theorization of Asian heroes and heroines beyond their mythic structure and folkloric limits. In considering the representation of heroes and heroines in the Asian folkloric tradition, and in comparative contexts, the book establishes connections between characters from myths and folktales and those found in contemporary narratives, considers the adaptation and transformation of heroes and heroines as revealed in a variety of literary works, and also assesses the gendering of social roles in modern literature and other art forms. It is of interest to scholars and advanced students in comparative literature, Asian cultural studies and theatre and performance. .